Bioactive coating as a surface modification technique for biocompatible metallic implants: a review - Priyadarshini, B.; Rama, M.; Chetan; Vijayalakshmi, U. (Journal of Asian Ceramic Societies, 2019)
Most high load-bearing implants are metallic alloys which contain toxic chemical components that might be released due to the corrosive environment of body fluids and load-bearing activity. Surface modification techniques do not guarantee biocompatibility. Hence, the bioactive surface of implants can be modified by coating the surface with a suitable material that addresses the needs of the patient. The choice and application process of the coatings should be determined based on the workability of the material and its physiochemical properties, such as the procedures involved and performance in avoiding removal of any desirable material properties that are helpful in the tissue regeneration process. Tailor-made coating materials prove very promising, as they might improve permanent implantations, make them more affordable and reduce the need for surgical revisions. The scope of the featured properties, such as addition of accelerated tissue regeneration, antibacterial properties and controlled release and removal of debris from the biological system to the metal implants makes coatings an ideal choice for surface modification of implants. This report reviews several options available for forming a biologically active layer over metallic surfaces that will interact with and produce desirable effects on host tissues.